Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1074/jbc.m116.737387
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation Impacts N-end Rule Degradation of the Proteolytically Activated Form of BMX Kinase

Abstract: Cellular signaling leading to the initiation of apoptosis typically results in the activation of caspases, which in turn leads to the proteolytic generation of protein fragments with new or altered cellular functions. Increasing numbers of reports are demonstrating that the activity of many of these proteolytically activated protein fragments can be attenuated by their selective degradation by the N-end rule pathway. Here we report the first evidence that selective degradation of a caspase product by the N-end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 47 publications
(54 reference statements)
0
21
0
Order By: Relevance
“…For example, many pro-apoptotic protein fragments generated by proteolytic cleavage have been demonstrated to be targeted for degradation via the N-end rule pathway (Ditzel et al 2003;Eldeeb and Fahlman 2016a;Eldeeb and Fahlman 2016b;Piatkov et al 2012a;Piatkov et al 2014;Xu et al 2012). In addition to this, there are examples demonstrating that the inhibition of the N-end rule or knockouts of components of the N-end rule pathway sensitize cells to cell stress and cell death (Agarwalla and Banerjee 2016;Deka et al 2016;Piatkov et al 2012a).…”
Section: The N-end Rule Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…For example, many pro-apoptotic protein fragments generated by proteolytic cleavage have been demonstrated to be targeted for degradation via the N-end rule pathway (Ditzel et al 2003;Eldeeb and Fahlman 2016a;Eldeeb and Fahlman 2016b;Piatkov et al 2012a;Piatkov et al 2014;Xu et al 2012). In addition to this, there are examples demonstrating that the inhibition of the N-end rule or knockouts of components of the N-end rule pathway sensitize cells to cell stress and cell death (Agarwalla and Banerjee 2016;Deka et al 2016;Piatkov et al 2012a).…”
Section: The N-end Rule Pathwaymentioning
confidence: 99%
“…Furthermore, it shall provide the molecular basis for a potential cellular mechanism that can regulate the degradation of a protein via post translational modifications that may be analogously identified in the future as we have previously demonstrated for an internal phosphorylation site modulating the degradation of the BMX kinase by the N-end rule pathway (Eldeeb and Fahlman 2016b). (Park et al 2015).…”
Section: Recent Work Bymentioning
confidence: 99%
“…At concentration of 20 µM for 1 , the ratio of G1-phase reached about 67.37%, which was about 12% higher than that of the control (55.75%) [ 17 , 18 ]. These data indicating that 1 may inhibit the growth of A549 cells through inducing apoptosis of tumor cells since G1 phase arrest was more related to cell apoptosis, and pro-apoptotic proteins like Bcl-2 usually plays key roles in accelerating the apoptosis of tumor cells [ 19 , 20 , 21 , 22 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…The N-end rule pathway recognizes specific N-terminal residues and ubiquitinates the proteins for proteasomal degradation [20]. If T24 cells had a mutation or modification, including phosphorylation in the N-terminal residues of the Dkk-3 protein, degradation of the Dkk-3 protein may delay and lead to its specific overexpression in T24 cells [21]. However, our data demonstrated that Dkk-3 protein in T24 cells was degraded by the proteasome as observed in 253JB-V cells.…”
Section: Discussionmentioning
confidence: 99%